Acceleration of Production Natural Disinfectants from the Combination of Eco-Enzyme Domestic Organic Waste and Frangipani Flowers (Plumeria alba) - Made Rai Rahayu; muliarta Nengah; Yohanes Parlindungan Situmeang (SEAS (Sustainable Environment Agricultural Science), 2021)
Spraying disinfectants is one of the efforts to prevent the transmission of COVID-19. One of the high needs for disinfectants can be overcome by using natural disinfectants or those made from natural ingredients, such as the use of eco-enzymes. The problem is that it takes 3 months to produce eco-enzyme, so it needs innovation to be able to produce it quickly. This research is an experimental study with independent variables, namely the composition of organic waste (rambutan fruit skin, corn cobs, chayote skin) as a substrate in varied eco-enzyme raw materials. Each treatment added 10% frangipani sandalwood extract. Control variables include fermentation time, water composition, brown sugar, yeast (Saccharomyches cerevisiae) with a fixed amount. The experimental results showed that the longer of fermentation time, the alcohol concentration increased, while the pH value decreased. The optimum time to produce eco-enzymes according to standard requirements for disinfecting purposes is 8-10 days, wherein the fermentation has produced an alcohol content of 60-70% and the pH of eco-enzymes has been reached below 4.0. The content of compounds in frangipani flower extract through phytochemical and GC-MS tests include terpenoids (linalool, geraniol, terpineol), quercetin from the flavonoid and citrulline groups of alkaloids and tannins which have various activities that support their role as a natural disinfectant including antibacterial, anti-fungi, and antivirals. The combination of Eco-Enzym from domestic organic waste and frangipani flower (Plumeria alba) is able to inhibit the growth of Staphylococcus aureus bacteria with very strong inhibition category ranging from 31.85-34.41 mm. Keywords: disinfectant, eco-enzyme, frangipani flowers